MAIN ASPECTS OF TEACHING MEDICAL TERMINOLOGY. - Kuziev Sarvarbek Ilmiddinovich (Western European Studies, 2023)
As this paper proposes, there's no characteristic deterrent to educating medical terminology inside the scope of an English course. Indeed lecturers who are not masters in medical sciences will discover educating the course, utilizing the numerous existing references and assets, or maybe straightforward.
Keywords: Medical Terminology; Methodology; Syntactic; Learning Challenge